The Influence of Digital Technologies on the Development of Smart Education in a Technologically Advanced Society - Voronkova, Valentyna; Nikitenko, Vitalina; Horodnycha, Svitlana; Kramar, Volodymyr; Stanislavova, Lyudmila; Khavina, Irina (Universidad del Zulia, 2023)
The purpose of the study is to conceptualize the impact of digital technologies on the development of smart education in a technologically advanced society. The model of adaptation of technologies to the education system is analyzed and the problems that arise in this process are identified. The essence and directions of digital education development as a factor in the development of smart education are revealed. The possibilities of using Facebook, Twitter, robotic platforms in the intelligent educational system, their tasks and objectives are shown. The object of the research is the development of smart education in a technologically advanced society. The subject of the study is the impact of digital technologies on the development of smart education in a technologically advanced society. The impact of digital technologies on the development of smart education in a technologically advanced society allows for cognitive mediation with students. Using digital technologies for interactive learning, students acquire new knowledge, deepen their education, develop creativity, become socially responsible citizens of the digital society, and form digital culture and thinking.

El propósito del estudio es conceptualizar la influencia de las tecnologías digitales en el desarrollo de la educación inteligente en una sociedad tecnológicamente avanzada. Se analizó el modelo de adaptación de la tecnología al sistema educativo y se identificaron los problemas que surgen en este proceso. Se revelan la esencia y las direcciones del desarrollo de la educación digital como factor en el desarrollo de la educación inteligente. Se muestran las posibilidades de uso de Facebook, Twitter, plataformas robóticas en el sistema educativo inteligente, sus tareas y objetivos. El objeto de la investigación es el desarrollo de una educación inteligente en una sociedad tecnológicamente avanzada. El tema de estudio es el impacto de las tecnologías digitales en el desarrollo de la educación inteligente en una sociedad tecnológicamente avanzada. El impacto de las tecnologías digitales en el desarrollo de la educación inteligente en una sociedad tecnológicamente avanzada permite la mediación cognitiva con los estudiantes. Mediante el uso de tecnologías digitales para el aprendizaje interactivo, los estudiantes adquieren nuevos conocimientos, profundizan su educación, desarrollan la creatividad, se convierten en ciudadanos socialmente responsables de una sociedad digital y forman una cultura y un pensamiento digitales.
La influencia de las tecnologías digitales en el desarrollo de la educación inteligente en una sociedad tecnológicamente avanzada
Keywords: digital technology; education; e-learning; online learning; social networks; tecnología digital; aprendizaje en línea; medios sociales